(untitled) (INTEGRATION PROCEEDING, 2023)
One of the uniqueness of Islamic Financial Institutions is the principle of profit sharing, especially mudharabah. Thepurpose of mudharabah is to provide compensation to the owner of the funds from the business results obtained by the fund managerwhose portion is agreed at the beginning, so that the results obtained from the owner of the funds are very dependent on the managerof the funds, the owner of the funds never asks for a defined reward in the form of an upfront nominal. The purpose of this study to analyze the practice of mudarabah financing at Bank Muamalat Indonesia.The study employs a quantitative descriptive research approach.The implementation of mudarabah financing at Bank Muamalat Indonesia has been carried out well. This can be seen from the accounts related to mudharabah financing transactions, accounting policies for mudharabah financings and disclosure of mudharabah financings in Bank Muamalat Indonesia’s financial statements.The limitations of this study are only using secondary data, while primary data is also needed such as interviews.This study provides a direct analysis of the financial statements of the companies studied that are rarely investigated by other researchers.